Editorial: Cancer genomics in the era of precision medicine - Omar M. Khan (17807774) (2024)
Cancer is a multifactorial disease driven by genetic and environmental factors, affecting a range of biological processes which regulate cell proliferation and survival. Advancements in sequencing technology and big data analysis have made genomics a key pillar of cancer research, providing insights into disease etiology, disease risk and treatment resistance mechanisms. In the clinical setting, cancer genomics is currently used to determine hereditary cancer risk, predict prognosis, and inform treatment selection. Other Information Published in: Frontiers in Genetics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fgene.2024.1378917